Imaging the essential role of spin-fluctuations in high-Tc superconductivity - Jenkins N.; Fasano, Yanina; Berthod C.; Maggio-Aprile I.; Piriou A.; Giannini E.; Hoogenboom B. W.; Hess C.; Cren T.; Fischer Ã˜.; Fasano, Yanina (American Physical Society, 2009)
Fil: Fasano, Y. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; University of Geneve; Suiza